Embeddedness of Creative Economy Actors in Creative Economy Development in West Sumatra Tourism Destination Areas - Irwan Irwan; Zusmelia Zusmelia; Ansofino Ansofino; Felia Siska (JED (Jurnal Etika Demokrasi), 2023)
Creative economy actors in West Sumatra have established relationships and have a sense of solidity in developing the creative economy. Creative economy actors in West Sumatra with a majority population of Minang make this cultural similarity the main capital in achieving togetherness, both in establishing cooperation and in the fields of production, distribution and consumption. Besides that, West Sumatra's creative economy actors build this attachment so that it creates the strength of shared capital in values, norms and networks. The focus of this research is to analyze the embeddedness of creative economy actors in the development of the creative economy in the tourist destination area of West Sumatra. This research focuses on the embeddedness theory proposed by Granovetter. This research uses a qualitative approach with a descriptive research type. The informants of this research are creative economy actors over 14 sectors in the tourist destination area of West Sumatra, with the withdrawal of informants using purposive sampling. The data collection method begins with secondary data collection with document studies, then in-depth interviews and non-participant observation. The unit of analysis in this study is an individual for economic actors in the West Sumatra tourist destination area. Data analysis uses the model of Miles and Hubermen by conducting 4 stages, namely data collection, data reduction, data presentation and conclusion drawing. The locations of this research are Padang City, Bukittinggi City, Sawahlunto City, South Coastal District and Tanah Datar Regency. The results of this study indicate that the embeddedness of creative economic actors in the development of EKRAF lies in regional relations of origin and family ties. Embeddedness is realized by the feeling of one ethnicity and blood ties.